Herpetología patagónica : X. El conjunto evolutivo de Liolaemus elongatus: análisis serológico - Cei, José Miguel Alfredo María (1975)
Serological and morphological observations support a natural phyletic stock of Patagonian Liolaemus, to which belong the elongatus complex, the kriegi-ceii complex and L. buergeri. The elongatus complex is a widespread species group, probably in active evolution. The serological polymorphism of the nominate form and the subspecies petrophilus is emphasized. The clear cut serological isolation of its allo-sympatrid cryptic form L. austromendocinus is pointed out. The serological relationships between the elongatus complex and the kriegi complex are briefly discussed.